KRISIS LINGKUNGAN AKIBAT SAMPAH DAN PENAMBANGAN EMAS ILEGAL PERAN MANUSIA DALAM MERUSAK ALAM - Sedia, Genopepa (Universitas Kapuas, 2025)
This research aims to identify the factors that cause the low level of safety of environmental defenders in Indonesia, as well as exploring the negative impacts of natural damage on communities and ecosystems. Apart from that, this research also provides an overview of the social, political and economic challenges faced by environmental defenders in the context of fighting against activities that destroy nature, as well as how policies and regulations related to the protection of environmental defenders need to be improved. The natural damage that occurs in Indonesia is greatly influenced by unsustainable natural resource exploitation practices, such as illegal mining, land clearing for plantations, and industrial activities that pollute the environment. However, environmental defenders who try to stop this destruction often face high risks, including legal and physical threats from parties who have an interest in destroying nature. In many cases, environmental defenders are often blamed or falsely accused, as well as persecuted or killed by parties who feel threatened by their cause.